Characterization and macrophages immunomodulatory activity of two water-soluble polysaccharides from Abrus cantoniensis - Qu, Dongshuai; Lian, Shuaitao; Hu, Hongjie; Sun, Wenjing; Si, Hongbin (Frontiers in Nutrition, 2022)
The aim of the study is to elucidate the physicochemical properties and immunomodulatory activity of two polysaccharides (ACPt0 and ACPt2) from Abrus cantoniensis. Results revealed that ACPt0 with a molecular weight of 26.0 kDa, was mainly composed of glucose (83.1%) and galactose (6.1%), and ACPt2 with a molecular weight of 145.6/8.9 kDa, consisted of galactose (25.6%), galacturonic acid (22.2%), arabinos (16.6%) and galactose (11.0%) respectively. AFM and Congo red experiments revealed that ACPt0 and ACPt2 might be spherical particles with triple-helix conformation in aqueous solution. ACPt0 and ACPt2 exhibited immunomodulatory activity by promoting the proliferation, augmenting pinocytic and phagocytic capacities, releasing immunoactive molecules such as ROS, NO, iNOS, TNF-α, IL-6 and IL-1β, upregulation of the mRNA levels of corresponding cytokines in macrophages. Moreover, ACPt0 and ACPt2 were recognized by toll-like receptor 4 (TLR4) and exerted immunomodulatory effects via activating Myeloid differentiation factor 88 (MyD88), mitogen-activated protein kinases (MAPKs) and serine/threonine kinase (Akt) signaling pathways in macrophages. Notably, ACPt2 had higher immunomodulatory activity than ACPt0. Based on the presentfindings, ACPt0 and ACPt2 had potent immunostimulatory activity and could be explored as an efficacious candidate for immunomodulators in the food and pharmaceutical fields.